Are we all on the same page? A qualitative study of the facilitation challenges associated with the implementation of deliberative priority-setting - Crompton, Amanda; Waring, Justin; Roe, Bridget; O’Connor, Rebecca (Taylor & Francis, 2017)
Collaborative governance has given rise to decision-making methodologies promoting democracy, inclusivity and transparency. This is exemplified by deliberative priority-setting (DPS) that blends cost-effectiveness analysis with stakeholder deliberation. Little is known however, about the facilitation challenges when ‘technical’ and ‘social’ elements are combined in a methodology. This paper investigates the facilitation challenges of implementing a DPS project within the English National Health Service (NHS). Our study examines the relationship between facilitation and the effectiveness of DPS processes, highlighting the importance of knowledge management as facilitators seek to translate technical information, to enhance the deliberative experience and promote legitimate decisions.